Implementation of human-machine friendship learning in the new-normal era - Saiful Bahri; Emi Tipuk Lestari (Journal of Education and Learning (EduLearn), 2021)
The 2019 coronavirus disease (COVID-19) pandemic outbreak has changed the conventional learning system to an online learning system. Online learning system is an alternative that can solve this problem with the principles of human-machine friendship learning (HMFL). This research was conducted to obtain an overview of the implementation of human-machine Friendship learning at IKIP PGRI Pontianak, Indonesia. Lecturers and students become research subjects, especially those in the History Education Study Program of the IKIP PGRI Pontianak. The research employed a qualitative approach with the type of phenomenological research. Data collection in this research was carried out by survey, interview and documentation. The results showed: (1) Implementation of HMFL of History Education Study Program of FIPPS IKIP PGRI Pontianak as a solution for implementing learning; (2) Effectiveness of Human-Machine Friendship Learning which is carried out in an effort to break the chain of the spread of COVID-19 using the application as a whole, students are satisfied with flexible learning; (3) The challenges of implementing HMFL include the weak supervision and control of students, the problem of weak internet signals, especially in rural areas, and the relatively high cost of internet quota.